Blood acetylcholinesterase activity is associated with increased 10 year all-cause mortality following coronary angiography. (November 2020) - Shenhar-Tsarfaty, Shani; Brzezinski, Rafael Y.; Waiskopf, Nir; Finkelstein, Ariel; Halkin, Amir; Berliner, Shlomo; Rogowski, Ori; Zeltser, David; Shapira, Itzhak; Laufer-Perl, Michal; Shacham, Yacov; Litmanowicz, Batia; et al.
Abstract: Background and aims: Parasympathetic dysfunction is associated with increased risk for major adverse cardiovascular events (MACE). However, clinically validated biomarkers that reflect parasympathetic activity are not yet available. We sought to assess the ability of serum cholinesterase activity to predict long term survival in patients undergoing coronary angiography. Methods: We prospectively followed 1002 consecutive patients undergoing clinically indicated coronary angiography (acute coronary syndrome or stable angina). We measured blood acetylcholinesterase (AChE) activity using the acetylcholine analog acetylthiocholine. Mortality rates were determined up to 10 years of follow-up. We divided our cohort into 3 groups with low, intermediate and high AChE activity by a Chi-square automatic interaction detection method (CHAID). Results: Patients with lower than cutoff levels of AChE (<300 nmol/min/ml) had higher mortality rates over 10 years of follow-up, after adjusting for conventional risk factors, biomarkers, clinical indication, and use of medications (HR = 1.6, 95% CI 1.1–2.5, p  = 0.02). Patients with intermediate levels of AChE (300–582 nmol/min/ml) were also at increased risk for death (HR = 1.4, 95% CI 1.1–1.9, p  = 0.02). AChE was inversely correlated with C-reactive protein, troponin I, fibrinogen and neutrophil/lymphocyte ratio levels. Conclusions: Patients presenting for coronary angiography with low levels of serum AChE activity are at increased risk for death during long term follow-up. Graphical abstract: Image 1 Highlights: We measured serum acetylcholinesterase activity in 1002 consecutive patients undergoing coronary angiography. Patients with low levels of acetylcholinesterase activity had higher mortality rates over 10 years of follow-up. Acetylcholinesterase activity was inversely correlated with inflammatory biomarkers such as CRP and neutrophil/lymphocyte ratio.